Fertility in men with primary ciliary dyskinesia presenting with respiratory infection. Issue 7 (July 1994) - Munro, N C; Currie, D C; Lindsay, K S; Ryder, T A; Rutman, A; Dewar, A; Greenstone, M A; Hendry, W F; Cole, P J
Abstract : BACKGROUND--Primary ciliary dyskinesia is characterised by chronic rhinosinusitis, chronic bronchial sepsis (usually with bronchiectasis), dextrocardia in approximately 50% of cases, and male infertility. The latter, described in patients attending infertility clinics, results from immotile but viable spermatozoa. Experience in a respiratory clinic suggests that infertility in men is not invariable. METHODS--The seminal fluid of 12 men with primary ciliary dyskinesia, six with dextrocardia, who presented consecutively with upper and lower respiratory tract sepsis was examined. Nasal ciliary beating was dyskinetic or absent in all cases, and nasal ciliary ultrastructure was abnormal in those 11 patients examined. RESULTS--Viable but immotile spermatozoa with abnormal tail ultrastructure were found in the ejaculate of only two patients. Two other patients had apparently fathered children; seminology in both these cases showed a normal spermatozoa count, one with normal spermatozoal motility and normal ultrastructure, the other with moderately reduced spermatozoal motility and abnormal ultrastructure (dynein arm deficiency on the peripheral microtubule doublets). A further two patients had normal spermatozoa counts, normal spermatozoa tail ultrastructure, and normal or only moderately reduced motility of spermatozoa. The spermatozoa of one patient were normally motile but there was severe oligozoospermia, and five patients were azoospermic. CONCLUSIONS--Not all men with primary ciliary dyskinesia have immotile spermatozoa. Seminal analysis is recommended in men with primary ciliary dyskinesia so that accurate counselling about reproductive capability may be given.